The Great Deluge: Hurricane Katrina, New Orleans, and the Mississippi Gulf Coast - Linda Foster Benedict (Journal of Applied Communications, 2006)
A book review of The Great Deluge: Hurricane Katrina, New Orleans, and the Mississippi Gulf Coast, by Douglas Brinkley.